Beyond irradiance: Visual signals influencing mammalian circadian function - Mouland, Joshua W.; Brown, Timothy M. (Circadian and Visual Neuroscience, 2022)
Daily changes in ambient illumination act as important time of day cues which are pivotal for aligning internal circadian clocks to external time. Melanopsin-expressing intrinsically photosensitive retinal ganglion cells (ipRGCs), generally considered specialized for encoding light intensity (irradiance), are critical to this photoentrainment process. However, ipRGCs also convey information from conventional photoreceptor cells, the rods and cones. Here we review data from animal studies identifying the nature and roles of rod and cone signaling to the suprachiasmatic nucleus (SCN) circadian clock including evidence that visual features other than irradiance (color, spatiotemporal variations in light intensity) may influence photoentrainment or other SCN-dependent functions. Finally we consider the extent to which these findings from animal studies might similarly apply to human circadian function.